Exploring the Interaction of Personality, Strategy, and Learning Environment in Achieving Success in Learning Arabic Grammar - Moh. Buny Andaru Bahy; Mohammad Samsul Ulum; Halimi Zuhdy; Aulia Rahman; Mirwan Akhmad Taufiq; Abdul Wahab Naf'an (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This study explored the interplay of personality, learning strategies, and learning environments in achieving success in Arabic grammar learning. A narrative inquiry approach was employed, with participants purposively selected based on their outstanding achievements in Arabic grammar competitions. Data were collected through in-depth interviews, and participants’ experiences were reconstructed and interpreted for analysis. The findings indicated that, in addition to effective instructional management and well-structured curriculum design, the integration of constructive personality traits, strategic learning approaches, and supportive learning environments significantly contributed to learners’ success in mastering Arabic grammar.